Balance of Obligations and Rights to Improve Education - Galih Putra Utama; Alamsyah Sastra Wijaya (Aslim: Journal of Education and Islamic Studies, 2025)
Education is a fundamental right of every citizen guaranteed by the constitution. However, its implementation requires a balance between the obligations and rights of various parties. This study aims to analyze how the balance between the obligations and rights of education providers can improve the quality of education in Indonesia. Using a qualitative approach with literature review and policy analysis methods, this study examines the roles of the government, teachers, students, and parents in the education ecosystem. The results indicate that the imbalance between obligations and rights is one of the factors hindering the improvement of education quality. The government has an obligation to provide access to quality education but is constrained by budget and infrastructure constraints. Teachers have professional obligations, but their welfare rights are not fully fulfilled. Students have the right to a decent education, but their obligation to learn is often neglected. Parents have an obligation to support their children's education, but their right to participate is limited. The results of this study can serve as recommendations for a policy framework that integrates obligations and rights proportionally to create a sustainable and quality education system.